Bioremediation of heavy metal contaminated aqueous solution by using red algae Porphyra leucosticta - Ye, Jianjun (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
Bioremediation is an effective process for the removal and recovery of heavy metal ions from aqueous solutions. In this study, red algae Porphyra leucosticta was examined to remove Cd(II) and Pb(II) ions from wastewater through biological enrichment and biological precipitation. The experimental parameters that affect the bioremediation process such as pH, contact time and biomass dosage were studied. The maximum bioremediation capacity of metal ions was 31.45 mg/g for Cd(II) and 36.63 mg/g for Pb(II) at biomass dosage 15 g/L, pH 8.0 and contact time 120 minutes containing initial 10.0 mg/L of Cd(II) and 10.0 mg/L of Pb(II) solution. Red algae Porphyra leucosticta biomass was efficient at removing metal ions of 10.0 mg/L of Cd(II) and 10.0 mg/L of Pb(II) solution with bioremediation efficiency of 70% for Cd(II) and 90% for Pb(II) in optimal conditions. At the same time, the removal capacity for real industrial effluent was gained at 75% for 7.6 mg/L Cd(II) and 95% for 8.9 mg/L Pb(II). In conclusion, it is demonstrated that red algae Porphyra leucosticta is a promising, efficient, cheap and biodegradable sorbent biomaterial for reducing heavy metal pollution in the environment and wastewater